2014
DOI: 10.15270/40-1-346
|View full text |Cite
|
Sign up to set email alerts
|

Strengths-Focused Intervention: The New Approach of the Social Work Service of the South African Police Service (Saps)

Abstract: Problem-solving skills: These include the ability to think abstractly, reflectively, the ability to be flexible and the ability to seek alternative solutions for both cognitive and social problems.Autonomy: This refers to a strong sense of independence, an internal locus of control, a sense of power, and self-esteem and self-efficacy.A sense of purpose and future: This refers to healthy expectations, a positive goal and success orientation, the will to be successful, educational aspirations, persistence, optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In 1991 social work became autonomous, with its own occupational class as part of the Human Resource Management structures (Stutterheim & Weyers, 2004:3).…”
Section: Historical Overviewmentioning
confidence: 99%
“…In 1991 social work became autonomous, with its own occupational class as part of the Human Resource Management structures (Stutterheim & Weyers, 2004:3).…”
Section: Historical Overviewmentioning
confidence: 99%
“…These are the factors that came out of the era of the South African Police (SAP) and those that pertain to the growth of the South African Police Service (SAPS) (1995 to present). In both cases the history will be divided into phases according to their most significant events (Ackerman, 1987;Ackerman, 2002;Dippenaar, 1988:244, 295, 429;Marais, 1988:15-20;Schoeman, 1996:50-56;Stutterheim & Weyers, 2002;Van der Merwe, 1985:10-26).…”
Section: Social Work In the Sap: 1952-1995mentioning
confidence: 99%
“…The completed research that has a bearing on some of the components of the accountability continuum (see Figure 1) includes: a study that led to the acceptance of the strengths-focused approach as the strategic service delivery paradigm for the Police Social Work section (Stutterheim & Weyers, 2004); a number of return-on-investment (ROI) studies that have a bearing on financial accountability and showed, among other things, that the organisation's investment in social work services is a "profitable endeavour" (Huisamen & Weyers, 2009:456-457;Williams & Weyers, 2009:380); a study into the effectiveness of EHW's Service (delivery) Information Record (SIR) system that has a bearing on the monitoring of the performance of its practitioners (Janse van Rensburg, 2012); and a large number of studies that dealt with the impact or effect of social work services on personnel and new recruits (Weyers, Huisamen, Kleingeld & Williams, 2006).…”
Section: Figure 1 the Accountability Continuummentioning
confidence: 99%
“…These varied from healthcare and nursing to psychology, and from human resources management to social work (Dauenhauer, Mayer & Mason, 2007:47-53;Grinnell, Gabor & Unrau, 2012:253-259;O'Brien & Stewart, 2009:109-117;Tilbury et al, 2010:81-87;Trotter, 2008:266-272;Van Nie, Hollands & Hamars, 2010:340-343). Sources also covered the nature of the SAPS and social work within this occupational setting, as well as previous research into the effect of social work services Janse van Rensburg, 2012;Stutterheim & Weyers, 2004;Weyers, Strydom, & Huisamen, 2008).…”
Section: Phase 1: the Literature Studymentioning
confidence: 99%